Lysosomal degradation of GMPPB is associated with limb‐girdle muscular dystrophy type 2T - Tian, Wo‐Tu (Ann Clin Transl Neurol, 2019)
OBJECTIVE: GDP‐mannose pyrophosphorylase B (GMPPB) related phenotype spectrum ranges widely from congenital myasthenic syndrome (CMS), limb‐girdle muscular dystrophy type 2T (LGMD 2T) to severe congenital muscle‐eye‐brain syndrome. Our study investigates the clinicopathologic features of a patient with novel GMPPB mutations and explores the pathogenetic mechanism. METHODS: The patient was a 22‐year‐old woman with chronic proximal limb weakness for 9 years without cognitive deterioration. Weakness became worse after fatigue. Elevated serum creatine kinase and decrements on repetitive nerve stimulation test were recorded. MRI showed fatty infiltration in muscles of lower limbs and shoulder girdle on T1 sequence. Open muscle biopsy and genetic analysis were performed. RESULTS: Muscle biopsy showed myogenic changes. Two missense mutations in GMPPB gene (c.803T>C and c.1060G>A) were identified in the patient. Western blotting and immunostaining showed GMPPB and α‐dystroglycan deficiency in the patient's muscle. In vitro, mutant GMPPB forming cytoplasmic aggregates completely colocalized with microtubule‐associated protein 1 light chain 3‐II (LC3‐II), a classical marker of autophagosome. Degradation of GMPPB was accompanied by an upregulation of LC3‐II, which could be restored by lysosomal inhibitor leupeptin. INTERPRETATION: We identified two novel GMPPB mutations causing overlap phenotype between LGMD 2T and CMS. We provided the initial evidence that mutant GMPPB colocalizes with autophagosome at subcellular level. GMPPB mutants degraded by autophagy‐lysosome pathway is associated with LGMD 2T. This study shed the light into the enzyme replacement which could become one of the therapeutic targets in the future study.